Perbedaan Efek Massage dan Swiss Ball Exercise Pada Kondisi Spondyloarthrosis Lumbal (Lembaga Penerbitan Universitas Esa Unggul, 2009)
Background : Lumbar Spondyloarthrosis is a common condition. Interventions provided by various methods such as providing one of the massage and exercise therapy with the use swiss ball. The methods of intervention would be chosen among the physioitherapist, but the empirical evidence on the subject is still very difficult to find. Objective : The purpose of this study was to detect differences between Massage and Exercise with Swiss Ball to the reduction of pain in the lumbar Spondyloarthrosis conditions. Method : This research uses quasi-experimental methods. The effects of differences in pain intensity reduction of 2 different groups with 8 people each group. Measuring of pain intensity using the Verbal Rating Scale (VRS). The effect of intervention to group I is to improvement of blood circulation, reduce pain sensory and supraspinal effect. On group II is to improve the ge-nerated reply circulation, reduce pain, supraspinal effect and improvement the stability of muscles. Data processing and analysis using statistical analysis with Mann-Whitney test and Wilcoxon match pairs test. Result : In the treatment group 1 found a significant decrease of pain between before and after treatment with p value = 0.016 (p <0.05). In group II found a significant decrease of pain before and after treatment with p value = 0.011 (p <0.05). Based on the data reduction of pain was group II much better than group I. Statistical analysis with Mann Whitney U test, get the p value = 0.015 (p <0.05).Keywords: Practice Model, Back Pain Under, Rattan Worker